Academic self-regulation as a crucial determinant of persistence intention: an empirical investigation with undergraduate Physics students: AUTORREGULAÇÃO ACADÊMICA COMO UM ELEMENTO IMPORTANTE DA INTENÇÃO DE PERSISTIR: UM ESTUDO EMPÍRICO COM ESTUDANTES DE GRADUAÇÃO EM FÍSICA - Vasconcelos do Evangelho Franco, Bianca (2024)
Proactive individuals consciously seek to develop self-awareness regarding their actions and behaviors to accomplish their goals. As they enhance their self-regulatory skills, they boost their motivation to learn and persist through their undergraduate studies. Motivation is a fundamental element in the learning process, influencing the student's decision to persist or dropout. Moreover, beliefs in self-efficacy, sense of belonging, and perception of curricular relevance also impact this decision, being considered predictors of student persistence. Based on the models of Zimmerman, Rosário, and Tinto, we investigated academic self-regulation and its relationship with persistence intention and other constructs. The data was collected through an online questionnaire, administered to 140 students of Physics courses. The results indicate that students tend to adopt self-regulatory behaviors related to the evaluation phase more frequently than those related to the planning phase. We have also identified significant correlations between the intention to persist and other constructs.